Emotions and identity issues in the hybridization of the Portuguese NHS hospitals: The case of activity-based costing implementation - Major, M.; Clegg, S.; Conceição, A. (45th EAA Annual Congress, 2023)
Drawing on Thornton et al. (2012) metatheoretical framework, which recognizes that institutional logics reside at different institutional levels and are linked by macro-micro, micro-micro and micro-macro interactions, this paper seeks to analyze the role of ABC technology in the hybridization of the Portuguese NHS hospitals field. In so doing we adopted a cross-level perspective so that the intra-organizational and field-level processes of hybridization could be brought together in the analysis. We report the results of a longitudinal and in-depth case study, encompassing the MoH and five public hospitals, conducted in the period between 2007 and 2015. Emotions and conflicts of identities prevented the use of ABC by the MoH to hybridize the sector and the medical profession. Actors’ identities and emotions played a central role in blocking the enactment of the managerialist logic by doctors, hence conditioning the hybridization outcomes at the field level. Recognizing that there is still little understanding of the dynamics of hybridization, we develop a cross-level perspective on these processes. Furthermore, we build critically on Thornton et al. (2012) arguing that emotions need to be explicitly incorporated in order that hybridization mechanisms are understood.